Electroconvulsive Therapy for Depression Comorbid With Myasthenia Gravis: A Case Report and Review of the Literature. Issue 1 (March 2018) - Warren, Mark B.; Elder, Scott; Litchfield, Norman P.
Abstract : Objectives: Myasthenia gravis (MG) is a rare but well-described autoimmune disease, which is sometimes comorbid with psychiatric illness. There have been several case reports describing the use of electroconvulsive therapy (ECT) for the treatment of core psychopathology in the context of MG. We sought to review the available published data on ECT in MG and add another case example to the literature. Methods: We performed a PubMed search for relevant articles or case reports in English describing ECT in MG and summarized findings. Results: We identified 7 published cases meeting our inclusion criteria in varying detail with different psychiatric presentations and different anesthetic and ECT technique approaches. In addition, we add our own case. Conclusions: Based on the literature and our own clinical experience, ECT seems to be a safe option for the treatment of core psychopathology with comorbid MG as long as appropriate precautions are in place, particularly when choosing an anesthetic approach.